Respondent-driven sampling (rds) as a new method to access vulnerable populations to hiv: its application in men who have sex with men - John H. Estrada M; Leonardo Vargas R (Universidad de Antioquia, 2010)
Approximately 30 million people are living with hiv all around the world in 2010. The most vulnerable hiv/aids groups are sex workers, intravenous drug users, transgender people and population of men who have sex with men (msm). Up to now, the surveillance and behavioral studies on sexual transmitted diseases (sti) and hiv have been conducted using intentional sampling methods like the snowball methodology, but this kind of sampling does not achieve representation and does not represent a conclusive method for the study of hidden populations in order to extend and apply its results to the general population. Furthermore, it is necessary to add to this limitation the lack of knowledge about the size of these groups that must face situations of stigma and discrimination. A decade ago a new method was designed to sample hidden and hard to reach populations based on Markov theories and on chain recruitment. This new method is known as respondent-driven sampling (rds) and it has been used in several behavioral and hiv prevalence studies. This review article presents the background, the theoretical support and a description of the method. It also analyzes some studies carried out using this new methodology.